THE CONCEPT OF REASONING IN ISLAMIC EDUCATION - Supriyatno, Triyo (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
This paper discusses the concept of reasoning in Islamic education. It focuses on explaining the role and significance of reasoning in the Islamic education legal requirements. The paper also examines various views of Scholars who approach the concept from perspectives other than that of Islam, where analysis is made in the light of the Quran and Sunnah for resolution. The paper repeats that sound reasoning is always consistent with the guidance of the Quran and Sunnah, a good believer therefore needs to examine the facts given by the Scripture to avoid a distorted view in analysis. Quran the Muslim Scripture has emphasized the significance of reasoning in substances of religion as well as in human’s life, the reasoning which receives guidance of the revelation and makes philosophy useful in human life and civilization.The best learners do not memorize random bits and pieces of information. Schools should produce students who are able to think, act, and handle situations or problems intelligently, and this is possible only if their thinking and problem solving skills are developed.